Using quality management procedures in education: Managing the learner‐centered educational environment - Stukalina, Yulia (Technological and Economic Development of Economy, 2010)
Now, the role of quality management in education is increasing. Managing for quality is now one of the major issues for educational organizations. One of the key tasks for education managers is to provide the learning process participants with an effective and motivating educational environment. Management of the educational environment presupposes giving a particular attention to students’ needs and requirements in order to improve educational practice and enhance educational quality. Among other things having their impact on the educational environment effectiveness is to what extent it motivates students for further studies. In this context, we regard student motivation as an essential factor for the educational environment quality improvement. This paper considers some quality management procedures that can be used by education managers to provide qualitative changes in the educational environment. To improve the quality of the educational environment we may use several management tools, regular educational environment evaluation being one of them. It includes collecting student feedback, which is a valuable source of analytical input in the process of the environment quality enhancement.Article in English.Kokybės valdymo procedūros taikymas mokymui: į mokinį orientuotos mokymo aplinkos valdymasSantrauka. Kokybės valdymo svarba švietimui pastaruoju metu išaugo. Ji yra viena iš pagrindinių švietimo organizacijų uždavinių. Svarbiausia švietimo vadybininkų užduotis ‐ mokymo proceso dalyviams sudaryti veiksmingą ir motyvuotą mokymo aplinką. Remiantis mokymo aplinkos valdymu, manoma, kad norint pagerinti mokymą ir pakelti mokymo kokybę reikia atsižvelgti į studentų poreikius bei reikalavimus. Vienas iš svarbiausių veiksnių, darančių įtaką mokymo aplinkos efektyvumui, yra studentų skatinimo toliau mokytis lygis. Remiantis šiuo kontekstu studento motyvacija laikoma esminiu veiksniu, padedančių pagerinti mokymo aplinkos kokybę. Norint pagerinti mokymo aplinką, galima naudoti keletą valdymo priemonių. Viena iš jų yra įprastos mokymo aplinkos įvertinimas. Ją sudaro mokinių grižtamasis ryšys, kuris yra vertingas šaltinis mokymo aplinkos kokybės gerinimo procese.Reikšminiai žodžiai: kokybės valdymas, švietimas, į moksleivį orientuota mokymosi aplinka, švietimas, mokinių grįžtamasis ryšys.First published online: 21 Oct 2010